ANALISIS PENERAPAN KESELAMATAN DAN KESEHATAN KERJA PADA PRAKTEK SISTEM KEMUDI, REM DAN SUSPENSI DI PROGRAM STUDI PENDIDIKAN TEKNIK OTOMOTIF UNIVERSITAS MUHAMMADIYAH PURWOREJO: K3 - Anitasari, Mike Elly; Widiyatmoko, Widiyatmoko (Universitas Negeri Yogyakarta, 2025)
The purpose of this study is to describe the knowledge, attitudes, and application of K3 in the practice of steering, brakes, and suspension systems of students of the Automotive Engineering Education Study Program, Muhammadiyah University of Purworejo (PTO Umpwr). This study is a descriptive study with a sample of 55 students. Data collection was carried out by observation, interviews, and questionnaires. Furthermore, the research data were analyzed using quantitative descriptive analysis techniques. The results of the study show that the K3 knowledge of PTO UMPwr students in the good category was achieved in all indicators. The average result of the overall K3 knowledge indicator in the good category was 81.62%. The students' K3 attitudes were in the good category, namely 85.4%. Based on the percentage of each attitude indicator, it is known that the highest percentage is the indicator of appreciation with a percentage of 96.2% in the good category and 3.80% in the fairly good category. While the lowest percentage is in the responding indicator where 82.2% are in the good category and 17.8% are in the fairly good category. The application of K3 in the practice of steering, brakes, and suspension systems shows a percentage score on each indicator reaching a score above 50%. The average result for